Criminal Responsibility of Influencers for Illegal Crypto Pump and Dump Schemes Under Indonesian Law - Yehezkiel Marbun; Rospita A Siregar (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the criminal liability of influencers in illegal crypto asset pump-and-dump schemes following the transition of oversight to the Financial Services Authority (OJK). Using a normative judicial method, it evaluates the synchronization between the EIT Law, the National Penal Code (Law No. 1/2023), and the P2SK Law. The results indicate that influencers can be held criminally liable under Article 28, paragraph (1) of the EIT Law for disseminating misleading information that causes material loss. Simultaneously, they may be prosecuted under Article 492 of the National Penal Code for fraud. The legal standing of influencers is constructed as "joint perpetrators" (medepleger) or "solicitors" (uitlokker) under Article 20 of the National Penal Code, given their dominant role in mobilizing the public through digital information manipulation. The use of disclaimers does not eliminate mens rea if criminal intent and profit from others' losses are proven. Integrative law enforcement is essential to protect consumers and the integrity of Indonesia's digital financial market